VD_FINDINFO Pron / 2011 / 31 vom 23. März 2011 - VD Tribunal cantonal (2011)
AUTORITÉ CANTONALE, VOIE DE DROIT, MESURE PROVISIONNELLE, ACTION EN DIVORCE | 117 CPC (CH), 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH), 405 al. 1 CPC (CH)